Studi Angka Lempeng Total (ALT) Mikroba dan Staphylococcus pada Mesin Fingerprint Perkantoran - Budi Triyantoro; Suparmin Suparmin; Dwi Bayu Karti Utami (Jurnal Riset Kesehatan, 2015)
This study aims to determine the relationship between ALT microbes and Staphylococcus aureus with the number of users of the fingerprint machine. The conclusion of the study show an increase in microbial ( ALT and Staphylococcus ) before and after the use of the fingerprint machine. However, no relationship was found between the number of users of the machine and the ALT and Staphylococcus (p=0,900 and  p=0,259). We suggest putting the fingerprint machine in a limited box or using the 3-dimensional sensor, fingerprint users should always wash their hands if they are going to eat or drink, as well as the need to disinfect the fingerprint scanner machine with 70 % alcohol before and after attendance services performed.